The impact of informational costs in quantity regulation of pollutants. The case of the European Emissions Trading Scheme - Peter Heindl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
There is extreme heterogeneity of firms regulated under the European Emissions Trading Scheme (EU ETS) in terms of emissions evels and employed technology. We present a model that shows that behavior of firms under quantity regulation can differ strongly, dependent on the characteristics of the firms when the assumption of full information is relaxed. If there are informational costs with regard to abatement options and costs, relatively small emitters and emitters with relatively complex technology will face a threshold for evaluating abatement options and costs. We compare the EU ETS to the US SO2 trading scheme and show that 'adjoining' markets to quantity regulation, supplying goods (i.e. abatement technology) or services (i.e. assistance in permit trading), play a crucial role to reduce transactions costs. Given high complexity of technology and/or strongly limited demand for certain technologies, markets will fail to provide appropriate assistance, generating efficiency losses. The presence of technological complexity and heterogeneous firms can have major consequences for the design of environmental regulation, when considering transaction costs.
urn:nbn:de:bsz:180-madoc-31927
Keywords: Q52; L22; O31; 330; Quantity Regulation; Transaction Costs; Technological Complexity; Induced Technological Change; Emissions Trading